Influence Of Purchasing Decisions Reviewed From Store Atmosphere, Promostions And Prices Perception (Survey Of Invesma Coffe House Consumers) - Puspita, Syaharani Anggi; Fitriadi, Budhi Wahyu; Patimah, Titin (Jurnal Fokus Manajemen, 2024)
The purpose of this study is to determine the influence of Store Atmosphere, Promotions and Prices Perception on Consumer Purchasing Decisions of Invesma Coffee House located on Jl. Bantargedang, Bungursari District, Tasikmalaya City. The method used in this study is a quantitative method with a survey approach to 100 respondents of consumers of Rumah Kopi Invesma. The types of data used are primary data and secondary data. The data analysis technique used is multiple linear regression analysis. The results of this test prove that Store Atmosphere, Promotions, and Prices have a significant effect both partially and simultaneously on Consumer Purchasing Decisions at Invesma Coffee House.